Formation of single and multi-walled carbon nanotubes and graphene from Indian bituminous coal. (1st May 2015) - Awasthi, Seema; Awasthi, Kalpana; Ghosh, A.K.; Srivastava, S.K.; Srivastava, O.N.
Highlights: We have synthesized single and multi-walled CNTs and graphene from Indian coal. Graphene sheets have been synthesized first time by arc discharge using coal electrode. The occurrence of several groups in coal has been confirmed by the FTIR spectra. A mechanism of CNTs formation from coal described here. Abstract: Single-walled carbon nanotubes (SWCNTs) have been synthesized by electric arc discharge method using annealed coal electrode in the presence of Fe as well as Ni–Y as catalysts. Multi-walled carbon nanotubes (MWCNTs) have been synthesized without using any catalysts. The efforts have also been made to synthesized graphene like nanosheets from bituminous coal. The as-synthesized samples have been characterized through scanning and transmission electron microscopy, Raman and Fourier transform infrared spectroscopy. The formation of SWCNTs which holds nearly perfect one dimensional structure is confirmed by the presence of radial breathing mode. A feasible mechanism of CNTs formation from coal described here with the help of Fourier transform infrared spectroscopy.